Extended quasiparticle approximation for relativistic electrons in plasmas - Morozov, V.G.; Ropke, G. (Condensed Matter Physics, 2006)
Starting with Dyson equations for the path-ordered Green’s function, it is shown that the correlation functions
for relativistic electrons (positrons) in a weakly coupled non-equilibrium plasmas can be decomposed
into sharply peaked quasiparticle parts and off-shell parts in a rather general form. To leading order in the
electromagnetic coupling constant, this decomposition yields the extended quasiparticle approximation for the
correlation functions, which can be used for the first principle calculation of the radiation scattering rates in
QED plasmas. Виходячи з рiвняння Дайсона для впорядкованої по контуру функцiї Грiна, показано, що кореляцiйнi
функцiї для релятивiстських електронiв (позитронiв) у слабозв’язанiй нерiвноважнiй плазмi можна
розкласти на квазiчастинковi частини та короткочасовi (off-shell) частини у досить загальнiй формi. З
точнiстю до головного порядку по електромагнiтнiй константi взаємодiї цей розклад дає розширене
квазiчастинкове наближення для кореляцiйних функцiй, яке можна використати для розрахункiв з
перших принципiв швидкостi розсiяння у КЕД плазмi.